((Legal means to confront the economic effects of the Corona pandemic)) "Iraq as example" - Zainab Abdul Kadhim Hassan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Covid 19 which was Confused in front of him the economies of the great powers, which led to the spread of corruption in the The economy of the great powers, It is always urgent, this dilapidated financial system for the positions that have been under popular pressure not so long ago, how much is it resistant to the economic repercussions of the Corona virus؟How have government measures affected the various groups of Iraqi society, especially those with limited income? And to what extent is the Iraqi and global economy affected by the new Corona virus? What are the legal means that enable countries, including Iraq, to ​​confront the negative economic effects of this virus? All these questions will be asked and answered in this research.